Emerging Synthesis Strategies of 2D MOFs for Electrical Devices and Integrated Circuits. Issue 33 (17th July 2022) - Wang, Linjuan; Saji, Sandra Elizabeth; Wu, Lingjun; Wang, Zixuan; Chen, Zijian; Du, Yaping; Yu, Xue‐feng; Zhao, Haitao; Yin, Zongyou
Abstract: The development of advanced electronic devices is boosting many aspects of modern technology and industry. The ever‐increasing demand for advanced electrical devices and integrated circuits calls for the design of novel materials, with superior properties for the improvement of working performance. In this review, a detailed overview of the synthesis strategies of 2D metal organic frameworks (MOFs) acquiring growing attention is presented, as a basis for expansion of novel key materials in electrical devices and integrated circuits. A framework of controllable synthesis routes to be implanted in the synthesis strategies of 2D materials and MOFs is described. In short, the synthesis methods of 2D MOFs are summarized and discussed in depth followed by the illustrations of promising applications relating to various electrical devices and integrated circuits. It is concluded by outlining how 2D MOFs can be synthesized in a simpler, highly efficient, low‐cost, and more environmentally friendly way which can open up their applicable opportunities as key materials in advanced electrical devices and integrated circuits, enabling their use in broad aspects of the society. Abstract : A framework of controllable synthesis routes for ultrathin 2D MOFs are discussed, followed by illustrations of promising applications relating to various electrical devices and integrated circuits. It is concluded by outlining how 2D MOFs can be synthesized in a simpler, highly efficient, low cost, and environmentally friendly way which opens up their opportunities in advanced electrical devices and integrated circuits.